Perbedaan Kebahagiaan Pasangan Pernikahan dengan Persiapan dan Tanpa Persiapan pada Komunitas Young Mommy Tuban - Fikriyyah, Wieda Rif"atil; Sakdiyah, Elok Halimatus (Jurnal Psikologi Tabularasa, 2015)
This study aimed to determine differences in happiness of married couples with preparation and without preparation. The subjects were members of the community Young Mommy Tuban (N= 44) . The method used was quantitative method with purposive sampling technique. Retrieving data using two scales, the scale adaptation of Authentic Happiness Scale developed by Martin Seligman (1980) consists of 23 items and the scale of Marriage Preparation which is based on the theory of Blood (1978), which consists of 26 item. The main analytical method used is the analysis of T-test. Based on the results of the study, showed that a married couple with the preparation had higher happiness than married couples without preparation. Resilience was found to be a major shaper aspects of happiness in a married couple with preparation and without preparation. Wedding happiness is found decreased based on length of marriage. The findings of other studies further discussed in the description below.